Toward understanding corruption concepts and perspectives of rural community leaders - Agaser, Nixon V. (Transactions of the National Academy of Science and Technology, 2011)
This paper investigates how community leaders think about corruption in Philippine society particularly corruption in government through simple interpretative phenomenological analysis (IPA). Eight rural community leaders (4 Barabgay captains and 4 Sanggunian Kabataan chairersons) participated in this study. Using in-depth interview, questions were focused on the "what" and why corruption persists in Philippine society. Interview texts were classified and interpreted following the basic steps used in IPA. Following bottom up approach, abstractions of meaning were done at two levels; text coding and thematic coding. Analysis reveals that corruption involves four basiv independent concepts namely; a)stealing government funds; b)abused of power; c)conspiracy of those who holds power, and; d)socio-cultural. In other words, rural community leaders think that corruption is an act of conspirarcy of those who holds power to steal goverment funds. Furthermore, community leaders thought that corruption has socio-cultural roots making it more difficult to solve. Participnats also thought that political power gives opportunity for corruption to thrive in governemt and that corruption and the corruption will perpetuate if those who are in power are "united" in carrying out corrupt practices. Solution in battling corruption, as indicated by the participants, still rest largely on goverment leaders. Conceptual and practical implications are discussed.